Philippine Islands, harbors of Palawan Island / published . by the Coast and Geodetic Survey, O.H. Tittmann, Superintendent - U.S. Coast and Geodetic Survey (Washington, D.C. : U.S. Coast and Geodetic Survey, 1905)
Relief shown by hachures and spot heights. Depths shown by gradient tints, soundings, and isolines Buoys shown in red, black, and white "Soundings and heights in feet." Includes text, seal, and tables "No. 4346" -- upper left margin "Published at Washington, D.C. August, 1905 ." Triangulation, topography, and hydrography executed in 1905 and 1906 West Coast of Palawan, Ulugan Bay (from a British survey in 1851) (scale 1:30,000) -- Southeast Coast of Palawan, San Antonio Bay (from a Spanish survey in 1888) (Scale 1:100,000) -- West Coast of Palawan, Culasian Bay (from a Spanish survey in 1889) (Scale 1:20,000) -- West Coast of Palawan, Malanut and Nakoda Bays (from Spanish survey in 1889) (Scale 1:30,000) -- East Coast of Palawan, part of Tapul Bay (from a Spanish survey) (Scale 1:20,000) -- Northwest Coast of Palawan, Bacuit (from a Spanish survey in 1877) (Scale 1:15,000) Color